Biomorphological peculiarities of the development of Spiraea L. genus species in the conditions of introduction on the South Coast of the Crimea - R.V. Galushko (Інтродукція Рослин, 1999)
The results of 10-years bioecological and rhythmological researches have been given for 26 species, forms and hybrids of genus Spiraea. Twenty species and forms can be recommended for use in ornamental gardening owing to long blossom period in summer, sufficient draught resistance and unpretentious ness to soils.